Preparation and Characterization of (MCM-41)-Eu2O3 Nanocomposite Materials - Zhai, Qing-Zhou; Li, Xiao-Dong (Asian Journal of Chemistry, 2011)
In the present study, a highly ordered mesoporous silica, nanoscale MCM-41, was synthesized and Eu2O3 was successfully prepared into the channels of nanoscale MCM-41 via the following methods: liquid-phase grafting method, thermal diffusion method and microwave-assisted synthesis method. The luminescence of Eu3+ is particularly interesting because Eu2O3 is one of the most important rare earth oxides and the major emission band is centered near 618 nm (red), which is one of the three primary colours (red, blue and green) from which a wide spectrum of colours can be generated by appropriate mixing. The Eu3+ ions show narrow emission bands arising from the 5DJ levels (J = 1, 2 and 3). Several characterization techniques were used to investigate physico-chemical properties of the prepared materials and to elucidate their luminescence properties. The prepared (MCM-41)-Eu2O3 nanocomposite materials have the ordered hexagonal mesostructure of MCM-41 and show the properties of luminescence. The detailed luminescence studies of all the nanocomposite materials show that (MCM-41)-Eu2O3 present stronger luminescent intensities and higher luminescent quantum efficiencies than bulk Eu2O3, indicating that the stability limitation of MCM-41 on the Eu2O3 in the channels is a benefit for the luminescence properties of the (MCM-41)-Eu2O3 nanocomposite materials. The emission spectra of (MCM-41)-Eu2O3 display the characteristic luminescence of Eu2O3 and the emission bands of (MCM-41)-Eu2O3 in the long wavelength are 5D0 ® 7FJ transitions of Eu2O3 in the nanoscale MCM-41. It is believed that a markedly enhanced emission occurs owing to the strong interaction between Eu2O3 and MCM-41. Meanwhile, the most effective preparative method (the microwave-assisted synthesis method) introduced in this paper is a very promising method for preparing (MCM-41)-Eu2O3 nanocomposite materials.